Perlindungan Hukum Peternak Ayam Terhadap Perjanjian Kemitraan Pola Inti Plasma dengan PT. LS - Nanda Revi Saputri; Riky Rustam (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study discusses legal protection for chicken farmers against the Core Plasma partnership agreement with PT. LS. The study was conducted on Hasoro, a broiler chicken farmer in Klaten, Central Java, who experienced legal problems due to the withholding of land certificates by PT. LS in the partnership agreement. The focus of the study includes the validity of the partnership agreement, the legality of PT. LS's actions in withholding land certificates, and the form of legal protection for farmers in partnership relations with Limited Liability Companies. The research method uses a legislative approach and a case approach, with data collection through document studies and interviews. The results of the study indicate that the partnership agreement between Hasoro and PT. LS does not meet the provisions of Article 1320 of the Civil Code because there are indications of a defective will and does not meet formal requirements. PT. LS's actions in withholding land certificates cannot be legally justified. This study recommends the need to strengthen regulations regarding partnership agreements so that farmers obtain legal protection, legal protection that has been provided by the government in addition to regulations, namely the role of the Business Competition Supervisory Commission. Settlement of this legal dispute can be resolved through litigation or non-litigation and the Government and related institutions must take an active role in implementing the partnership agreement in order to provide fair benefits for all parties involved.